A simple drought risk analysis procedure to supplement water resources management planning in England and Wales - Turner, Sean W. D.; Jeffrey, Paul (Wiley, 2020)
The current ‘Deployable Output’ approach for assessing water resources system performance in England and Wales is a practical, communicable means for assessing the adequacy of a water supply system and determining the relative benefits of proposed system enhancements. A recognised flaw with this approach is that it fails to characterise the severity of potential supply shortfalls, leading to mischaracterisation of risks and benefits associated with alternative candidate investments. Here, we propose a Monte Carlo procedure that could supplement the existing process by exposing the magnitude (% water demand unserved) and duration (number of days) of supply curtailments under a range of drought scenarios. The method is demonstrated using a realistic, stylised water resources system and a discrete number of infrastructure investments. Results demonstrate that vulnerability assessments can expose previously unidentified risks that might radically alter a planner’s estimate of the cost‐effectiveness of a particular investment.
Keywords: water resources systems analysis; vulnerability; stochastic hydrology; risk assessment